Low-vacuum scanning electron microscopical characteristics of small cell carcinoma and lymphoma in pleural fluid specimens - SOEJIMA, Yurie; UCHIYAMA, Masayuki; YANO, Tetsuya; NAKAJIMA, Yutaka; MOCHIZUKI, Renon (Japanese Journal of Medical Technology, 2025)
Objective: We examined the cell morphology in pleural effusion using low-vacuum scanning electron microscopy (LVSEM) to differentiate small cell carcinoma (SmCC) and lymphoma. Study Design: Our study included pleural fluid specimens from 16 cases, including seven cases of SmCC and nine cases of lymphoma. The specimens were examined and photographed under an optical microscope, and the cover glasses were removed using hot xylene. After conductive staining with phosphotungstic acid, the same specimens were observed, and photographs were obtained by LVSEM. Results: Differentiation between SmCC and lymphoma was impossible in five cases using an optical microscope alone. On LVSEM, SmCC cells showed “dome-like cell morphology” (85.7%), “high density microvilli” (85.7%), “cell binding positive” (85.7%), and “depression” (42.9%), while lymphoma cells showed a “spherical morphology” (100%), “short microvilli” (88.9%), and “cell binding negative” (88.9%). Differentiation was performed in 14 cases using LVSEM. Conclusion: Our findings suggest that using LVSEM in the cytopathological examination of pleural fluid is useful for distinguishing SmCC and lymphoma.